Legal Protection for the Winners of the Execution of Mortgage Rights in the Auction Case of Blocking of Property Rights Certificates (SHM) which Become the Object of the Auction - Rizky Melani Dian Pratiwi; Hanif Nur Widhiyanti; Diah Aju Wisuwardani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to examine the meaning of the phrase